Do structural changes in the tumour bed after intraoperative radiotherapy (IORT) of breast cancer complicate the evaluation of mammograms in a long-term follow-up? - Wasser, Klaus; Ruch, Markus Michael; Brade, Joachim; Schoeber, Carola; Kraus-Tiefenbacher, Uta; Schnitzer, Andreas; Engel, Dorothee; Wenz, Frederik; Sütterlin, Marc; Schönberg, Stefan; Büsing, Karen-Anett (European journal of radiology, 2012)
The purpose of the study was to assess whether postoperative changes in the tumour bed after intraoperative radiotherapy (IORT) with low-energy X-rays complicate the mammographic evaluation. 54 patients receiving breast-conserving surgery and IORT were compared to a control group of 48 patients with conventional breast-conserving treatment. All patients were included in routine follow-ups (≥3 years) with mammography accompanied by ultrasound. By retrospective consensus reading the mammographic changes in the tumour bed were classified as absent, low or distinct. Using the same grading it was classified whether mammographic evaluation was complicated due to postoperative changes. Focusing the yearly follow-ups within a period of four years, distinct changes were found significantly more often after IORT (52-62% vs. 7-30%). After IORT the evaluation was significantly more often distinctly complicated in each follow-up, except for year 1 (16-21% vs. 0-8%). In the IORT group the distribution of findings was nearly stable over time. In the control group it changed over time and a distinctly complicated evaluation was no longer seen in the follow-ups of years 3 and 4. Overall, further non-routine diagnostic procedures due to unclear findings in the tumour bed became necessary in 7% (IORT) vs. 8% (control group) of the patients (p=0.86). Evaluation of mammograms is complicated after IORT. In contrast to conventionally treated patients postoperative changes and difficulties of evaluation do not decrease over time. Overall, after IORT the diagnostic uncertainty does not seem to be increased in ultrasound supported mammographic follow-ups. The topic needs further evaluation with larger study samples.
Available online 4 March 2011
Gesehen am 28.11.2018